Desenvolvimento de audição e linguagem em crianças surdas implantadas: Análise de resultados a partir do edal-2 - Martins Filho, Renato Riesemberg Gabriel (2017)
The advent of compulsory newborn hearing screening of August 2010 facilitated access to diagnosis, indication and early intervention for children with hearing loss. Advances in the technology of hearing aids and the growing recognition of the effectiveness of cochlear implants for both adults and children, allied to the policy of the Brazilian Unified Health System with the free supply of these prostheses, has led to an increase in the number of children implanted in the public and private hearing health services. Evaluating and monitoring the audiological profile of these children is fundamental for the success of speech therapy for the development of hearing and oral language. In Curitiba, the Pequeno Príncipe Hospital, which works with the pediatric population, perform implants since 2010, where due to this necessity, its team of speech therapists developed the Scale of Hearing and Language Development, a protocol composed of 4 tests, which evaluates the benefits of the cochlear implant in the first years after implantation. Objective: To analyze the results of hearing and language development in implanted deaf children, with hearing age between two and five years, through the Scale of Hearing and Language Development. Method: Three studies were carried out to achieve this objective: 1- Systematic review of literature to determine the protocols used to evaluate hearing and language of the pediatric population in the routine of Brazilian cochlear implant services; 2 - Application of the Scale of Hearing and Language Development - part 2, in normal hearing children, aged between two and five years, to establish the normality curve of the test; 3 - Application of the Scale of Hearing and Language Development - part 2, in implanted children with hearing age between two and five years, to characterize the hearing and language performance compared to the group of normal hearing children. This is an experimental study of a descriptive nature. The study included 126 children divided into two groups: control with 102 normal hearing children, and study with 24 deaf implanted children. Results: It was found that in the Brazilian scenario there is a great heterogeneity of protocols being used to evaluate hearing and language in the routine of Brazilian cochlear implant services, especially with the pediatric population, most of them being of foreign origin. It was possible to determine the normality curve of the Scale of Hearing and Language Development - part 2, on hearing children, and to compare the results of deaf implanted children. The protocol proved to be effective with regard to a rapid verification of hearing and oral language development. Conclusion: The study allowed verifying that implanted children have lower responses when compared to their hearing peers, but their development is increasing as their age and hearing experience increase.